Kajian Semantik Nama Tua Warga Dusun Duwet Gentong, Kalurahan Srimulyo, Kapanewon Piyungan, Kabupaten Bantul - Shaputra, Avinda Shalwa; Wulan, Sri Hertanti (LOKABASA, 2025)
Penelitian ini mengkaji semantik nama tua warga Dusun Duwet Gentong, Kalurahan Srimulyo, Kapanewon Piyungan, Kabupaten Bantul. Nama tua dipilih sebagai fokus penelitian karena selain menjadi identitas diri, juga mengandung makna atau simbol tertentu. Jenis penelitian ini adalah deskriptif kualitatif dengan pengumpulan data melalui open dokumen, kuesioner, dan wawancara dengan narasumber yang memiliki atau mengerti nama tua. Data dianalisis secara deskriptif kualitaitf dengan validitas triangulasi sumber dan reliabilitas intrarater serta interrater. Hasil penelitian menunjukkan bahwa nama tua terbentuk dari varian jumlah kata ada yang satu kata, dua kata, dan tiga kata, wujud satuan lingualnya antara lain monomorfemis, polimorfemis serta rangkaian monomorfemis dan polimorfemis. Makna leksikal, gramatikal, dan kontekstual, digunakan untuk mengetahui dasar pemberian nama tua. Dasar dari pemberian nama tua di temukan dari unsur harapan (kesejahteraan, kepintaran, percintaan, kebaikan, kekuatan, kewibawaan, keindahan, kekayaan, kebahagiaan), unsur penanda agama, unsur nama kecil, unsur gaib, penanda sejarah, unsur objek alam, dan unsur nama wayang. This study examines the semantics of traditional names among the residents of Duwet Gentong Hamlet, Srimulyo Village, Piyungan District, Bantul Regency. Traditional names were chosen as the focus of the research because, in addition to serving as personal identifiers, they also carry specific meanings or symbolic significance. This is a qualitative descriptive study, with data collected through open documents, questionnaires, and interviews with individuals who have or understand traditional names. The data were analyzed using a qualitative descriptive approach, supported by source triangulation for validity and both intrarater and interrater reliability checks. The findings reveal that traditional names consist of varying word counts—one, two, or three words—and appear in different linguistic forms, including monomorphemic, polymorphemic, and combinations thereof. Lexical, grammatical, and contextual meanings are used to understand the underlying reasons for name assignment. The basis for assigning traditional names includes elements of hope (such as prosperity, intelligence, love, kindness, strength, authority, beauty, wealth, happiness), religious markers, childhood names, mystical elements, historical references, natural objects, and names derived from wayang (Javanese shadow puppetry) characters.